Formato e área de comedouros em tanques-rede para alevinos de tilápia do Nilo - Mahl, Ilson (2010)
This study aimed to evaluate formats and areas of feeders used in cages on production performance, uniformity of lots, physical and chemical characteristics and body indexes of Nile tilapia. It was used 2700 juvenile of tilapia with mean weight of 5.95 ± 1.23 g, distributed in 27 cages (0.5 x 0.5 x 1.0 m) in a completely randomized design in a factorial model, feeders with two formats (square and circular) and four areas (100, 75, 50 and 25%) and a control (feeder free) with three replications. After 64 days evaluated the performance parameters of weight gain, total length, specific growth rate, survival, feed conversion and uniformity of lots. The levels the dry matter, crude protein, ether extract and ash were evaluated from the eviscerated fish. The viscerossomatic, hepatossomatic and visceral fat indexes were also evaluated. The format of feeders did not influence (P>0.05) the performance parameters of tilapia juvenile, however, the feeders area did affect (P<0.05) the survival, with the highest 98.3% for feeders with area of 50%. It was observed lower values of weight gain (25.45 g) and length (11.50 cm) of fish reared in cages at absent of feeders. The feed conversion was higher (P<0.05) for fish in cages without feeder compared to the others. The fish reared in cages with square feeders with area of 75% and reared absent of feeders showed the highest humidity levels of 71.27% and 74.13% respectively. The interaction format and area also influenced (P<0.05) the crude protein of fish, with values of 17.02% and 17.34% respectively for cultures containing feeders circular with area of 75%, and squares with area of 50%. There were no significant differences (P>0.05) for mineral matter, however fish cultured in cages containing squares feeders with area of 100% and circular with area of 50% showed higher values (P<0.05) respectively, 8.83% and 9.48% for ether extract. The format and the area of feeders did not affect (P>0.05) at corporeal indexes, however, fish subjected to cages without feeders had lower hepatossomatic index, viscerossomatic and visceral fat (P<0.05), with values of 10.87, 2.36 and 2.33% respectively. The different areas and formats feeder does not interfere in the productive performance on stage of juvenile Nile tilapia in cages with small volume. Whereas to better utilization of diets on the fish performance it is recommended to use at least one of combinations of size and format of feeder used during cultivation.